Conductive Aerogels: Amyloid Fibril‐Templated High‐Performance Conductive Aerogels with Sensing Properties (Small 45/2020). Issue 45 (12th November 2020) - Han, Yangyang; Cao, Yiping; Bolisetty, Sreenath; Tian, Tian; Handschin, Stephan; Lu, Canhui; Mezzenga, Raffaele
Abstract : Aerogels are ultralight solid materials formed by replacing the liquid phase found in hydrogels by air. In article number 2004932, Canhui Lu, Raffaele Mezzenga, and co‐workers show that using protein amyloid nanofibrils as templates, it is possible to design a new class of high‐performance conductive aerogels for smart devices, such as biosensors, wearable bioelectronics, pressure sensors and adaptable microsystems.